2017
DOI: 10.21767/1791-809x.1000472
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Evaluation of Environmental Tobacco Smoke: Gender and Socioeconomic Disparities in a Low Income Country-Palestine

Abstract: Background: Approaching high socioeconomic females' group toward environmental tobacco smoking (ETS) has little been studied. Our aim was to assess the high educated females' knowledge, attitudes and avoidance behavior towards ETS exposure to appropriately focus the targets in smoking prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 20 publications
4
15
2
Order By: Relevance
“…Teachers' knowledge of SHS Less than two-thirds of the participants (63.2%) were in the 'Good Knowledge' category. The findings from this study corroborate previous studies carried out among highly educated participants, namely, university employees 22 and university students 19 , whereas low levels of knowledge were noted in studies in low education groups 18 . This study revealed that almost all the respondents were aware that SHS contains toxic chemicals (98%) and that it is harmful to the health of passive smokers (99%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Teachers' knowledge of SHS Less than two-thirds of the participants (63.2%) were in the 'Good Knowledge' category. The findings from this study corroborate previous studies carried out among highly educated participants, namely, university employees 22 and university students 19 , whereas low levels of knowledge were noted in studies in low education groups 18 . This study revealed that almost all the respondents were aware that SHS contains toxic chemicals (98%) and that it is harmful to the health of passive smokers (99%).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the relatively high avoidance levels were recorded in the study conducted by Nuzooa 19 among university students in Mauritius. However, previous studies among highly educated subpopulations like women working at universities 21,22 showed low levels of avoidance despite the level of knowledge of SHS displayed. Conversely, studies carried out among subpopulations, like general public 18 and adolescents 28,29 , with lower levels of knowledge of SHS, showed adequate levels of avoidance.…”
Section: Teachers' Behaviour Towards Shsmentioning
confidence: 70%
See 2 more Smart Citations
“…The present research showed that women are more exposed to ETS at home, than men. In some other research, Al-Zabadi et al in Palestine observed that more than half of the participants admitted that a family member or a spouse also consumed tobacco and they, thus, were exposed to ETS [39]. Contrary to the present ndings, Skorge et al [40]., Alamgir Kabir et al [41].…”
Section: Discussioncontrasting
confidence: 76%